Tailoring porosity in carbon materials for supercapacitor applications - Borchardt, Lars; Oschatz, Martin; Kaskel, Stefan (Materials Horizons, 2014)
Within the different available electrochemical energy storage systems, supercapacitors stand out due to their high power densities and ultra-long cycle life. Their key-components are the electrode materials where the charge accumulation takes place and therefore many different approaches for the synthesis of carbonaceous electrode structures with well-defined pore systems are available. This review focuses on different strategies for tailoring porous carbon materials from the micropore level, over mesopores to macropores and even external or inter-particular porosity. A wide range of materials such as activated carbons, templated carbons, carbide-derived carbons, carbon nanotubes, carbon aerogels, carbon onions, graphenes and carbon nanofibers are presented, always in relation to their pore structure and potential use in supercapacitor devices.
CRIS-Team Scopus Importer:2023-03-20